1997
DOI: 10.1038/sj.jhh.1000485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-arginine on systemic and renal haemodynamics in salt-sensitive patients with essential hypertension

Abstract: In response to a high sodium (Na + ) intake, salt-sensitive in salt-resistant (؉55 ؎ 16.0 ml/min/1.73 m 2 ) and saltsensitive patients (؉22 ؎ 21.5 ml/min/1.73 m 2 ). patients with hypertension retain more Na + and manifest a greater rise in arterial pressure than salt-resistant This study has shown that salt-sensitive AfricanAmericans manifest different systemic and renal patients. Because there is limited information regarding the role of nitric oxide (NO) in salt-sensitivity we examhaemodynamic responses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 2 publications
1
26
0
2
Order By: Relevance
“…This putative NO deficit may be responsible for their endothelial dysfunction, which in turn may contribute to SSBP by impeding vasodilation after a salt load. 49 4. The sympathetic nervous system: Several investigators showed that in an SS substrain of SHR, the pressor response to salt was associated with increased levels of plasma and urine catecholamines 50 and renal nerve activity, 51 whereas alterations in hypothalamic norepinephrine turnover with decreased norepinephrine content suggested diminished central sympathetic inhibition of peripheral sympathetic outflow.…”
Section: Elijovich Et Al Salt Sensitivity Of Blood Pressure E11mentioning
confidence: 99%
“…This putative NO deficit may be responsible for their endothelial dysfunction, which in turn may contribute to SSBP by impeding vasodilation after a salt load. 49 4. The sympathetic nervous system: Several investigators showed that in an SS substrain of SHR, the pressor response to salt was associated with increased levels of plasma and urine catecholamines 50 and renal nerve activity, 51 whereas alterations in hypothalamic norepinephrine turnover with decreased norepinephrine content suggested diminished central sympathetic inhibition of peripheral sympathetic outflow.…”
Section: Elijovich Et Al Salt Sensitivity Of Blood Pressure E11mentioning
confidence: 99%
“…Infusion of L-arginine, the substrate for NOS, evokes a blunted renal vasodilatory response in patients with salt-sensitive versus salt-resistant hypertension and controls. 35 This implies the existence of a specific renal NO defect in salt sensitivity. Although the issue of salt sensitivity was not specifically addressed, Cardillo et al 36 observed reduced NO-dependent vasodilator activity in the forearm circulation during mental stress in blacks.…”
Section: Discussionmentioning
confidence: 99%
“…High salt intake initially stimulates NO production (to maintain normotension despite increase in blood volume caused by increased salt intake) to maintain blood flow, and only when the enhanced salt intake continues for a long time, NO synthesis is decreased (possibly because of the exhaustion of the eNOS activity), which leads to the development of hypertension (Nakanishi et al, 2002). On the other hand, supplementation of L-arginine reduces high salt intakeinduced hypertension (Campese et al, 1997;Bayorh et al, 1999). Vasodilation to acetylcholine increases with potassium chloride supplementation, in patients with hypertension (Taddei et al, 1994), which explains its mild to moderate antihypertensive action.…”
Section: No and Hypertensionmentioning
confidence: 99%